2002
DOI: 10.1073/pnas.202296599
|View full text |Cite
|
Sign up to set email alerts
|

Fluid flow increases mineralized matrix deposition in 3D perfusion culture of marrow stromal osteoblasts in a dose-dependent manner

Abstract: Bone is a complex highly structured mechanically active 3D tissue composed of cellular and matrix elements. The true biological environment of a bone cell is thus derived from a dynamic interaction between responsively active cells experiencing mechanical forces and a continuously changing 3D matrix architecture. To investigate this phenomenon in vitro, marrow stromal osteoblasts were cultured on 3D scaffolds under flow perfusion with different rates of flow for an extended period to permit osteoblast differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

48
524
6
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 632 publications
(590 citation statements)
references
References 40 publications
(49 reference statements)
48
524
6
2
Order By: Relevance
“…Differences in geometrical configurations of perfusion bioreactor systems and the complex internal architecture of scaffolds (Bancroft et al, 2002;Bonvin et al, 2010;Wendt et al, 2003;Zhao and Ma, 2005) makes correlating observed biological outcomes on the basis of inlet fluid flow-rate very difficult. Calculation of the  within systems allows comparisons to be made on a single representative scale.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in geometrical configurations of perfusion bioreactor systems and the complex internal architecture of scaffolds (Bancroft et al, 2002;Bonvin et al, 2010;Wendt et al, 2003;Zhao and Ma, 2005) makes correlating observed biological outcomes on the basis of inlet fluid flow-rate very difficult. Calculation of the  within systems allows comparisons to be made on a single representative scale.…”
Section: Discussionmentioning
confidence: 99%
“…However, static culturing regimes neglect the important role of biomechanical stimuli in the normal formation, development and homeostasis of bone tissue: the effects of which are clearly observed when normal, physiologically relevant levels of mechanical stimulation are removed (Morey and Baylink, 1978;Zerwekh et al, 1998). Therefore, in-vitro bone tissue cultivation strategies have sought to enhance the osteogenic differentiation of cell-seeded constructs by employing mechanical stimulation via flow-perfusion (Bancroft et al, 2002;Cartmell, S. et al, 2003;Keogh et al, 2011;Sikavitsas et al, 2003;Sikavitsas et al, 2005;Vance et al, 2005). We have successfully employed an in-house designed perfusion bioreactor to examine the effects of mechanical stimulation on gene expression levels of key osteogenic markers for MC3T3 (pre-osteoblasts) cell-seeded collagen-GAG (CG) scaffolds subjected to a range of fluid flow regimes and for exposure times of 1h to 14 days Partap et al, 2009;Plunkett et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Abousleiman and Sikavitsas, 2006;Cimetta et al, 2007;Kim et al, 2007). For small tissue-engineered constructs these methods have been shown to be successful in comparison to static culture (Glowacki et al, 1998;Goldstein et al, 2001;Bancroft et al, 2002;Cartmell et al, 2003). However, problems arise when the tissue size is scaled up.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, constructs are grown under perfusion conditions either in a columnar (3) or rotating bioreactor (4) to promote the formation of bone throughout the scaffold. A better understanding of the regulatory role of various endogenous growth factors and mechanical loading conditions could greatly improve the quality of bioreactor-derived bone (5).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the continuous perfusion of the cells attached to the fiber surface will promote the appositional growth of bone in the radial direction, resulting in more mineralized tissue compared to monolayer cultures or cells seeded onto highly porous polymer meshes cultured under static conditions (3,7). Lastly, bone cells are expected to thrive within the HFBR system because the cells experience fluid shear stresses (3,(7)(8)(9)(10)(11). The drawback of this HFBR system is the inability to sample the tissue as it forms in the reactor.…”
Section: Introductionmentioning
confidence: 99%